2014
DOI: 10.1126/scisignal.2005191
|View full text |Cite
|
Sign up to set email alerts
|

PIP4kγ is a substrate for mTORC1 that maintains basal mTORC1 signaling during starvation

Abstract: Phosphatidylinositol-5-phosphate 4-kinases (PIP4ks) are a family of lipid kinases that specifically use phosphatidylinositol 5-phosphate (PI-5-P) as a substrate to synthesize phosphatidylinositol 4,5-bisphosphate (PI-4,5-P2). Suppression of PIP4k function in Drosophila results in smaller cells and reduced target of rapamycin complex 1 (TORC1) signaling. Here we showed that the γ isoform of PIP4k stimulated signaling through mammalian TORC1 (mTORC1). Knockdown of PIP4kγ reduced cell mass in cells in which mTORC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…These results, along with a recent observation that the enzyme encoded by this gene is a substrate of mTORC1 (6), suggest a close relationship between mTORC1 and Pip4k2c. Moreover, the hyperimmune phenotype of the Pip4k2c −/− mice could be partially ameliorated by treatment with the mTORC1 inhibitor, rapamycin.…”
Section: Significancesupporting
confidence: 71%
See 3 more Smart Citations
“…These results, along with a recent observation that the enzyme encoded by this gene is a substrate of mTORC1 (6), suggest a close relationship between mTORC1 and Pip4k2c. Moreover, the hyperimmune phenotype of the Pip4k2c −/− mice could be partially ameliorated by treatment with the mTORC1 inhibitor, rapamycin.…”
Section: Significancesupporting
confidence: 71%
“…The fact that PI5P4Kγ has very low activity compared with PI5P4Kα and PI5P4Kβ but forms heterodimeric complexes with these active enzymes suggests that its major role is to regulate the localization and/or activity of PI5P4Kα and PI5P4Kβ. As discussed in the introduction, it was reported by Mackey et al (6) that PI5P4Kγ is phosphorylated by mTORC1 on S324 and S328. Interestingly, Mackey et al (6) found that expression of a S324A/ S328A double-mutant form of PI5P4Kγ in HeLa cells enhanced mTORC1 signaling, whereas expression of a phosphomimetic mutant (S324D/S328D) suppressed mTORC1 signaling.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…While the 4E-BPs are responsible for many of the effects of mTOR on protein translation, the La related protein 1 (LARP1) is a recently discovered mTORC1 effector which also represses the translation of TOP mRNAs (Fonseca et al, 2015). Another novel mTORC1 substrate discovered recently is the phosphatidylinositol-5-phosphate 4-kinase γ (PIP4Kγ) (Mackey et al, 2014). Finally, a major new transcriptional effector of TORC1 signaling was identified this year in Drosophila melanogaster , REPTOR (Tiebe et al, 2015).…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 99%